MOTIVASI KUNJUNGAN WISATAWAN KE OBJEK WISATA KELUARGA ANDALUS KABUPATEN KAMPAR PROVINSI RIAU - Dea Marlita; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Motivation is an important factor for prospective tourists in making decisions about tourist destinations to be visited. This research was conducted in order to determine the motivation of tourist visits to the Keluarga Andalus tourism object in Kampar Regency, Riau Province. In this study, researchers used mixed methods. Researchers collected data by means of questionnaires, interviews, observations, documentation and literature studies. The technique for determining the sample uses the Slovin formula with a measurement scale, namely the Likert scale. The samples in this study were 100 samples who were tourists from the Keluarga Andalus tourist attraction. The results of this study resulted in physical motivation getting a score of 1,925, cultural motivation getting a score of 1,058, interpersonal motivation 1.157, status and prestige motivation getting a score of 1,832. Thus, the motivation for tourist visits to Keluarga Andalus Tourism Objects in Kampar Regency, Riau Province, visits on the basis of having physical motivation, which tourists can carry out various physical activities at Keluarga Andalus attractions. This requires the manager of the Keluarga Andalus attraction to further improve the attractions that can be done by tourists at the Andalus Family attraction, so that tourists who have visited the Keluarga Andalus attraction want to make a return visit. Keywords: Motivation, tourists, tourist motivation, Keluarga Andalus tourism